Dynorphin B induces lateral asymmetric changes in feline spinal cord reflexes - Vereshchaka, Inna; Kostyukov, Alexander (Frontiers in Neuroscience, 2013)
The effects of dynorphin B (an agonist of κ-opioid receptors) and naloxone (an antagonist of opioid receptors) on the field potentials (FPs) evoked in the lumbar spinal cord of spinalized cats were examined following successive stimulation of pairs of identical peripheral nerves on both sides of the body. The FPs were recorded bilaterally using microelectrodes from symmetrical sites of the gray matter between the L6 and L7 segments of the spinal cord transected at level of Th11. Significant changes (up to 75%) were registered in the areas of the initial positive components of the FPs evoked by sequential stimulation of the nn. gastrocnemius-soleus, flexor digitorum longus, and tibialis at both hind limbs; a difference between the effects of various nerves was not observed. Two-Way ANOVA analysis showed that two factors, the injection type and recording side, as well as a combination of these factors, strongly influenced the amplitudes of the FPs. Statistically significant side- and injection-dependent differences were registered in the majority of the tests. Both the directions of the changes in the FPs and their relative amplitudes were not strongly connected with a definite side of the spinal cord in different animals. Therefore, it is possible to postulate that the κ-opioid receptors are distributed inhomogeneously over the neuronal populations transmitting the peripheral afferent signals from different hind limbs, thus indicating a possible presence of the lateral asymmetry effects.